Factors causing the death of Kabesak (Acacia leucophloea Roxb. Willd.) seedlings in the monsoon tropical forest of Timor Island - Arnold C. Hendrik; Novi I. Bullu (Foresty Faculty of Hasanuddin University, 2021)
Regeneration of kabesak (Acacia leucophloea) in the primary forest of the Timor Island regenerationis dominated by tree stands than seedlings and saplings. Seedling and sapling supplies are very important for regulating or maintaining plant populations and their adaptation to environmental changes. This study aims to determine the effect of shades, herbivores, and seedlings height on the survival and growth of Kabesak seedlings in natural forests in Timor Island. The research was conducted in dry season, from July to December 2020. The stages in this study were determining the research location and selecting kabesak seedlings that grew in nature, marking and measuring of height of the selected kabesak seedlings. Data collection was done eight times with interval of three weeks including number of dead seedling and number of leaves for live seedlings. The results showed that the presence of shade can reduce the effects of drought, thereby increasing the survival of seedlings in the natural habitat of deciduous tropical forests. Apart from shading factors, seedling height during the dry season also affect the survival of kabesak seedlings, where there was no dead seedling with 15 cm or more height. The herbivores in this study were not found to be the main cause of death for seedlings. To ensure the survival of kabesak seedlings in their natural habitats, it is necessary to avoid kabesak seedlings < 15 cm from the effects of long-term drought, as well as from herbivores and fires.